Perceptions and Experiences of Flipped Learning in English Language Teaching Departments in Indonesia: - - Jati, Sigit Pramono; Ritonga, Mhd Rasid; Budiono, Mohamad (PANYONARA: Journal of English Education, 2025)
This paper aims to explore the perceptions and experiences of flipped learning in English teaching classes in Indonesian universities. Firstly, it explores the implementation of flipped learning worldwide in the context of English teaching. Afterwards, interviews will be conducted with the heads of departments with at least one lecturer implementing flipped learning and students who are taught using flipped learning in their English classes. From the literary works, it is found that flipped learning’s benefits are in line with the need to improve Indonesian English Language Teaching. Regarding the drawbacks, flipped learning is not against the regulations of higher education institutions. Instead, it enforces the policies decreed in the university context. According to the heads of the departments, flipped learning will be more widely accepted in the future. However, there is one big concern regarding resources, particularly in remote areas. The students report better learning experiences, but also complain about study load, time limitations, IT issues, language barriers, and distractions. In addition, the student-participants also suggest being facilitated with more feedback and interactive yet meaningful activities in class.